Spiritual Psychotherapy for Schadenfreude Behaviour of Adolescents on Digital Trends - Hasanah, Iswatun; Anna Aisa; Imaniyatul Fithriyah (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2022)
Digital trends with many teenagers who are active in social media from various platforms innovate and create to be able to become FYP (For Your Page) shows, presenting pro-con content by involving the sadness and misfortune of others and even enjoying the condition of others who are experiencing problems has become a common phenomenon among adolescent content creators. The feeling of pleasure derived from the sadness of others and the lack of empathy is a Schadenfreude behavior related to the self-esteem of the individual. This study aims to find out how the process and effectiveness of the application of Islamic psychotherapy in reducing Schadenfreude behavior in adolescent content creators in Pamekasan Regency. The method used in this study was a descriptive qualitative method with a case study. The process of collecting data on this research was carried out by means of observation, interviews and documentation of the process of applying spiritual psychotherapy. The data sources in this study involved four adolescents of the male sex who became activists of social media content creators, both tiktokers, YouTubers, or celebgrams, as well as literature as secondary data. Data analysis was performed using Miles and Huberman models. The conclusions obtained from this study are: 1) Schadenfreude's behavior carried out based on rivalry, which is more individualistic and related to interpersonal competition (both between friends and between content creators) 2) The spiritual psychotherapy model given to four respondents, namely including meditation therapy, fardu and zikr prayer therapy, and Qur'an therapy 3) The success of the application of the spiritual psychotherapy model in four respondents was generally quite successful. i.e. minimizing Schadenfreude's behavior. All four respondents showed positive changes in both individual self-esteem, emotions, behavior and in the frequency of worship.